Menyibak Pelaporan Aset Bersejarah Berdasarkan Psap No. 07 Tahun 2010 (Studi Fenomenologi Pada Candi Penataran Blitar-Jawa Timur) - Diana Elvianita M (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2016)
Historic assets are historic buildings, monuments, archaeologicalplaces like temples, and the work is focused on reporting seni.Penelitianhistoric assets Temple Penataran.Candi Penataran selected as the objectof this study, because the temple Upgrading an historic assets inIndonesia and is the largest in the temple kemplek East Java. It is hopedthat by doing this research can provide answers on "How to implementPSAP No. 7 of 2010 as a basis for Historic pelaporanAset "with theapproach of Phenomenology on Penataran Temple Blitar, East Java.